(untitled) (Journal of Analytical Oncology, 2015)
Purpose:Ifosfamide can cause an unexplained encephalopathy. The incidence after intravenous infusion is 10%, but is much higher after oral administration. This study assesses the pharmacokinetics of oral ifosfamide in relation to neurotoxicity. Patients and Methods:Eleven patients received oral ifosfamide 500 mg twice daily for 14 days, with concurrent oral mesna. The concentrations of ifosfamide, isophosphoramide mustard, 2-dechloroethylifosfamide, 3-dechloroethylifosfamide, carboxyifosfamide, ketoifosfamide, chloroethylamine and 3-oxazolidine-2-one were measured using GC-MS. Patients were evaluated clinically, and also with the EEG, psychometric testing, the national adult reading test, and the mini-mental state examination. Results:A decrease in the electroencephalogram alpha frequency was observed, with the development of pathological slow wave activity. Psychometric performance was also impaired. Neurotoxicity was progressive during treatment, and the incidence of grade 3 neurotoxicity was 22%. The mean day 14 / day 1 Cmax ratios for 2-dechloroethylifosfamide and 3-dechloroethylifosfamide were 2.73 (± 2.11) and 2.04 (± 1.32) respectively. The metabolite with the lowest ratio was isophosphoramide mustard 1.07 (± 0.39). High chloroethylamine Cmax values were associated with lower alpha frequencies, and increased clinical neurotoxicity. Conclusion:Oral ifosfamide 500 mg twice daily for 14 days causes unacceptable neurotoxicity. It was not possible to identify one particular metabolite responsible for the neurotoxicity, although the dechloroethyl metabolites and chloroethylamine are implicated.